Radiometric dating of late Quaternary loess in the northern piedmont of South Tianshan Mountains: Implications for reliable dating. (1st February 2018) - Song, Yougui; Luo, Dan; Du, Jinhua; Kang, Shugang; Cheng, Peng; Fu, Chaofeng; Guo, Xiaohua
Abstract : Reliable chronologies are prerequisites when interpreting proxy records in terrestrial archives of Quaternary climate and environmental change. Optically stimulated luminescence (OSL) dating and accelerator mass spectrometry radiocarbon dating (AMS 14 C) are commonly used to date late Quaternary loess deposits in the Chinese Loess Plateau, but the range and reliability of the two methods in Central Asia are still debated. In this study, we investigate both fine‐grained quartz OSL and AMS 14 C dating of a late Quaternary loess section located at the northern piedmont of the South Tianshan Mountains in Central Asia and discuss the reliability of the two radiometric dating methods. The results show that the OSL and AMS 14 C ages are generally consistent with the stratigraphic sequence when the ages are younger than 25 cal ka BP, which means that both can be used to establish a reliable chronology in the Ili Basin. But beyond this age, the OSL dating method seems to be a more reliable approach. The results also supported previous dates based on medium‐grained quartz OSL dating of the Ili loess in the southern piedmont of the North Tianshan Mountains. Radiocarbon ages older than 25 cal ka BP should be treated with caution, and attention must be paid to the influence of pedoturbation on OSL signals in the Central Asian loess. Multiple dating approaches for mutual authentication and exploring new dating materials are suggested in further loess chronological research. These findings will be helpful in establishing a reliable timescale and in reconstructing high‐resolution environmental change in Central Asia.